2017
DOI: 10.1016/j.jallcom.2017.04.201
|View full text |Cite
|
Sign up to set email alerts
|

Size effects of ferroelectric and magnetoelectric properties of semi-ellipsoidal bismuth ferrite nanoparticles

Abstract: Bismuth ferrite (BiFeO 3 ) is one of the most promising multiferroics with a sufficiently high ferroelectric (FE) and antiferromagnetic transition temperatures, and magnetoelectric (ME) coupling coefficient at room temperature, and thus it is highly sensitive to the impact of cross-influence of applied electric and magnetic fields. According to the urgent demands of nanotechnology miniaturization for ultra-high density data storage in advanced nonvolatile memory cells, it is very important to reduce the sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…All that stimulated us to study the influence of size effects on the FE, AFE, and ME properties of semiellipsoidal BiFeO 3 nanoparticles theoretically, in the framework of the Landau-Ginzburg-Devonshire approach, classical electrostatics, and elasticity theory [128]. Ferroelectricity is known to be a phenomenon associated with the long-range ordering of dipole moments.…”
Section: Motivation and Formulation Of The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…All that stimulated us to study the influence of size effects on the FE, AFE, and ME properties of semiellipsoidal BiFeO 3 nanoparticles theoretically, in the framework of the Landau-Ginzburg-Devonshire approach, classical electrostatics, and elasticity theory [128]. Ferroelectricity is known to be a phenomenon associated with the long-range ordering of dipole moments.…”
Section: Motivation and Formulation Of The Problemmentioning
confidence: 99%
“…If the magnetization M is proportional to the applied magnetic field H, i.e. ≈ FM ( ) , the PME coefficient has the form [128]…”
Section: Motivation and Formulation Of The Problemmentioning
confidence: 99%
“…The continuum phenomenological Landau-Ginzburg-Devonshire (LGD) approach combined with the electrostatic equations allows one to establish the physical origin of the anomalies in the polar and dielectric properties, and calculate the phase diagrams changes appearing under the decrease of ferroelectric particle sizes. For instance, using the LGD approach Niepce [20], Huang et al [21,22], Glinchuk et al [23,24], Ma [25], Khist et al [26], Wang et al [27], Morozovska et al [28,29,30,31] and Eliseev et al [32,33,34] have shown, that the changes of the transition temperatures, enhancement or weakening of spontaneous polar or/and magnetic order in a single-domain spherical, ellipsoidal and cylindrical nanoparticles of sizes (4 -100 nm) are conditioned by the various physical mechanisms, such as surface tension, correlation effect, depolarization field, flexoelectricity, electrostriction, magnetoelectric coupling, magnetostriction, rotostriction and Vegard-type chemical pressure. We emphasize that the applicability of the LGD approach for ferroelectric nanoparticles with sizes about (4-5) nm or more (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete screening of spontaneous polarization causes depolarization fields, which in turn can lead to appearance of ferroelectric domains in the particle, decreasing the positive energy of depolarization field [26,27,33,34,44]. Incomplete screening conditions of the spontaneous polarization also leads to the decrease of ferroelectric transition temperature due to the depolarization field effect [26,27,33,34]. Yet the vast majority of theoretical models (both LGD-based and ab initio) consider the particles covered with perfect electrodes, stabilizing their single-domain state (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These properties facilitate the magnetic (spin) state control by electric fields, with some having the potential to be used in multistate logic sensors, non-volatile memories, solid-state transformers, and electromagneto-optic actuators [1,2,3,4,5,6]. Among multiferroic materials, BiFeO 3 (BFO) has been intensively investigated due to its unique characteristics of a high ferroelectric–paraelectric transition temperature ( T C ) of approximately 1083 K, and high antiferromagnetic to paramagnetic Néel temperature ( T N ) of approximately 625 K [7,8,9,10]. However, it is well known that BFO causes high leakage currents and magnetic measurement errors that have been attributed to specific structural defects [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%